Chemotaxonomic significance of limonoids and triterpenoids from Dictamnus angustifolius G. Don ex Sweet. (April 2015) - Lv, Meng-ying; Tang, Ben-qin; Teng, Jing; Liang, Jing-yu; Xu, Feng-guo; Zhang, Zun-jian; Sun, Jian-bo
Abstract: Phytochemical investigation of the root bark of Dictamnus angustifolius G. Don ex Sweet (Rutaceae) resulted in the isolation and characterization of three degraded limonoids (1 –3 ), five limonoids (4 –8 ) and four triterpenoids (9 –12 ). All structures were elucidated on the basis of spectral analysis. Among them, compounds4, 6, 8, 9 and12 were isolated from the genus Dictamnus for the first time. Compounds10 and11 were obtained from D . angustifolius for the first time. Moreover, the chemotaxonomic significance of these compounds was summarized. Graphical abstract: Eight limonoids and four triterpenoids were isolated from Dictamnus angustifolius . Limonoids4, 6, 8 and triterpenoids9, 10 were isolated from the genus Dictamnus for the first time. Triterpenoids10 and11 were isolated from Dictamnus angustifolius for the first time. The chemotaxonomic significance of the isolates was discussed. Highlights: Eight limonoids and four triterpenoids were isolated from Dictamnus angustifolius . Limonoids4, 6, 8 and triterpenoids9, 10 were isolated from the genus Dictamnus for the first time. Triterpenoids10 and11 were isolated from Dictamnus angustifolius for the first time. The chemotaxonomic significance of the isolates was discussed.